Influence of family communication features on building a baby voice interaction with peers - Гончаренко, Алла (Educological discourse, 2013)
Article considers dependence of dialogue in a family from its structure, character of social roles, related communications and influence of such system of interpersonal mutual relations on formation at the child of the relation to coevals.